2018
DOI: 10.7567/1347-4065/aaeb49
|View full text |Cite
|
Sign up to set email alerts
|

Kilowatt-level, high brightness, narrow-linewidth polarization-maintained fiber amplifiers based on laser gain competition

Abstract: Stimulated Brillouin scattering (SBS) management in kilowatt-level, high brightness, narrow spectral width, and all polarization-maintained amplifiers using laser gain competition is demonstrated. This method can increase the SBS threshold of the fiber amplifier by more than double without changing the linewidth. By further incorporating the phase modulation technique, the SBS threshold is scaled to be as high as 32.4 times compared to the single frequency amplification. An output power of 1082 W is achieved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Generally, the high-power narrow linewidth PM fiber lasers are based on a master oscillator power amplifier (MOPA) structure. Until now, several types of seed have been used in narrow linewidth PM MOPAs, mainly including a phase modulated single-frequency laser (PMSFL) seed [10][11][12][13][14], superfluorescent (SF) seed [15], a random fiber laser (RFL) seed [16] and a fiber oscillator laser (FOL) seed [17][18][19][20]. In 2017, Su et al reported a 2.43 kW all-PM fiber laser with 68 GHz (0.255 nm) linewidth based on a PMSFL seed [11].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the high-power narrow linewidth PM fiber lasers are based on a master oscillator power amplifier (MOPA) structure. Until now, several types of seed have been used in narrow linewidth PM MOPAs, mainly including a phase modulated single-frequency laser (PMSFL) seed [10][11][12][13][14], superfluorescent (SF) seed [15], a random fiber laser (RFL) seed [16] and a fiber oscillator laser (FOL) seed [17][18][19][20]. In 2017, Su et al reported a 2.43 kW all-PM fiber laser with 68 GHz (0.255 nm) linewidth based on a PMSFL seed [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, stimulated Brillouin scattering (SBS) [7] and mode instability (MI) [8] effects will limit the power scaling of PM narrow linewidth single mode fiber laser. In the last few years, researchers made great progress on power scaling of narrow linewidth PM fiber lasers [9][10][11][12][13][14][15][16][17][18][19]. In 2008, Nufern Company achieved a kilowatt PM fiber laser output with a linewidth less than 10GHz [9].…”
Section: Introductionmentioning
confidence: 99%